Children's mental health: a priority to consider - Jorge Javier Caraveo-Anduaga; Nora Angélica Martínez-Vélez (Instituto Nacional de Salud Pública, 2019)
Objective. To identify possible changes in the frequency of psychopathological syndromes in Mexican children population over a 15-year period using the Brief Screening and Diagnostic Questionnaire (CBTD in Spanish). Materials and methods. Information gathered from different studies on the general population, schools and medical general practice are analyzed. Results from the Mexico City study were used as base rates for comparisons. Results. Higher prevalence of externalizing syndromes such as attention deficit and hyperactivity, oppositional and explosive conduct were very evident. Also, anxiety and depressive syndromes showed a notable increase. Prevalence of abnormal language and probable epilepsy were also increased on different age-groups. Conclusions. Findings are discussed in light of longitudinal reports in the literature as well as on reports in adolescent population in Mexico.